ОБРАЗ ЗМЕИ У ТЮРКО-МОНГОЛЬСКИХ НАРОДОВ - Шолахов , М.Г.; Набиев , Р.А. (Asian Journal "Steppe Panorama", 2026)
Abstract. Introduction. The image of the snake is one of the most ancient and universal symbols present in the cultures of the peoples of Eurasia. Among Turko-Mongolian peoples, it occupied a significant place in mythological, folkloric, and religious representations. The symbolism of the snake was formed under the influence of archaic beliefs associated with shamanism, totemism, and the cult of nature. Of particular interest is how the image of the snake was perceived in oral traditions, beliefs, taboos, and zoomorphic representations of Turko-Mongolian peoples. Written sources, ethnographic materials, and folklore data make it possible to trace the main forms of understanding the snake in traditional culture. Research Objectives. The aim of the article is to analyze the image of the snake among Turko-Mongolian peoples. The main objectives include identifying representations of the snake in written and ethnographic sources, determining its place in mytho-ritual practices, and conducting a comparative analysis of the most common interpretations of this image. Results. The study established that the image of the snake had an ambivalent character and could be perceived as a sacred, dangerous, or forbidden creature. It was revealed that in some cases the significance of the snake was noticeably exaggerated in folk superstitions and archaic beliefs formed under the influence of shamanism and totemism. Conclusions. The image of the snake among Turko-Mongolian peoples reflected not only ancient mythological ideas but also persistent superstitious attitudes in which the sacred role of animals was often exaggerated.